Rekonstruksi Prinsip Itikad Baik dalam Transaksi Bisnis Digital di Era Ekonomi Platform - Asriyani, Arini; Murdiono, Murdiono; Prabowo, Rahmat Eko; M.A, A.P. Jaya Negara (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This article examines the transformation of the good faith principle in Indonesian contract law in response to the rise of platform-based digital business transactions. It identifies a fundamental tension between the classical, text‑oriented understanding of good faith in the Civil Code and the structural realities of the platform economy, where contracts are formed and performed through algorithms, standard‑form clauses, and interface design. Using a normative juridical method with statutory, conceptual, and case approaches, the study analyzes civil law doctrines, Indonesian legislation on electronic transactions and consumer protection, as well as contemporary scholarship on good faith, dark patterns, and digital contract governance. The findings show that, in its current formulation, the good faith principle remains too abstract and remedial, so it is unable to address asymmetric power, information, and technological control embedded in digital platforms. The study therefore proposes a reconstruction of good faith as a structural governance standard that operates ex ante at the level of contract design and platform architecture, anchored in transparency, fairness in design, and proportional risk allocation. Such a reconceptualization would guide legislators, courts, and platform providers in developing concrete benchmarks for lawful digital practices, enabling good faith to function as an effective safeguard of contractual justice and consumer protection in the platform economy.